2015
DOI: 10.18632/oncotarget.5920
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA-212 negatively regulates starvation induced autophagy in prostate cancer cells by inhibiting SIRT1 and is a modulator of angiogenesis and cellular senescence

Abstract: Among a number of non-coding RNAs, role of microRNAs (miRNAs) in cancer cell proliferation, cancer initiation, development and metastasis have been extensively studied and miRNA based therapeutic approaches are being pursued. Prostate cancer (PCa) is a major health concern and several deregulated miRNAs have been described in PCa. miR-212 is differentially modulated in multiple cancers however its function remains elusive. In this study, we found that miR-212 is downregulated in PCa tissues when compared with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(46 citation statements)
references
References 51 publications
(75 reference statements)
2
42
0
Order By: Relevance
“…The role of SIRT1 in tumors is significantly heterogeneous. In prostate cancer, SIRT1-mediated autophagy plays a role in modulating angiogenesis and cellular senescence [35], while in human breast adenocarcinoma MCF7 cells, it promoted autophagosome maturation and tumor growth [23]. It has also been reported that SIRT1 could promote autophagosome maturation by deacetylating Beclin-1 [23].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The role of SIRT1 in tumors is significantly heterogeneous. In prostate cancer, SIRT1-mediated autophagy plays a role in modulating angiogenesis and cellular senescence [35], while in human breast adenocarcinoma MCF7 cells, it promoted autophagosome maturation and tumor growth [23]. It has also been reported that SIRT1 could promote autophagosome maturation by deacetylating Beclin-1 [23].…”
Section: Discussionmentioning
confidence: 99%
“…In our previously published study, we showed that SIRT1 regulates autophagy through the SIRT1-FoxO1-Rab7 axis, deacetylation of ATGs 5, 7, and 8 and other mediators, such as H4K16ac, FoxO3, E2F1, and p73 [17]. Recently, Ramalinga et al (2015) [35] demonstrated that miR-212 inhibits autophagy by inhibiting SIRT1 expression in prostate cancer cells, while transfection of cells with SIRT1 induced autophagy. In addition, SIRT1 could reduce polyglutamine cellular toxicity by inducing autophagy in SH-SY5Y cells [36].…”
Section: Discussionmentioning
confidence: 99%
“…32 SIRT1, which was shown to modulate both physiological and pathological processes in cells via acting on cell cycle proteins, including Rb, is now verified to be targeted by miR-212 in some cancers. 33,34 miR-212-3p was shown by Ramalinga et al 35 to prevent autophagy and angiogenesis while inducing cellular senescence by targeting SIRT1 in PCa. Likewise, it was demonstrated that miR-212-3p can suppress thyroid cancer cell growth through SIRT1.…”
Section: Mir-212 and The Cell Cyclementioning
confidence: 99%
“…Many of these processes require the modulation of autophagy by SIRT1 (12, 40, 126, 127). SIRT1 controls stem cell survival by modulating autophagic flux (128) and SIRT1 activity is increased in conjunction with AMPK to lead to autophagy and cellular protection (129).…”
Section: Circadian Rhythm Mtor and Sirt1mentioning
confidence: 99%